2022
DOI: 10.1021/acsnano.2c07785
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down Approaches for 10 nm-Scale Nanochannel: Toward Exceptional H2S Detection

Abstract: Metal oxide semiconductors (MOS) have proven to be most powerful sensing materials to detect hydrogen sulfide (H 2 S), achieving part per billion (ppb) level sensitivity and selectivity. However, there has not been a way of extending this approach to the top-down H 2 S sensor fabrication process, completely limiting their commercial-level productions. In this study, we developed a top-down lithographic process of a 10 nm-scale SnO 2 nanochannel for H 2 S sensor production. Due to high-resolution (15 nm thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…Kang et al demonstrated that the H 2 S sensor performance can be drastically enhanced with the NiO nanoheterojunction ( R a / R g = 166.2, τ res = 21 s at 0.5 ppm). 17 Zhu et al prepared a kind of 3.9% Ag@UG-NiO sensor whose response to 100 ppm butanone was about 3.1 times higher than that of pure porous spherical NiO. 18 Currently, according to literature reports, researchers have improved the response value and recovery speed of sensors by constructing heterostructures, 19 metal ion doping, 20 regulating the micromorphology 16 and light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Kang et al demonstrated that the H 2 S sensor performance can be drastically enhanced with the NiO nanoheterojunction ( R a / R g = 166.2, τ res = 21 s at 0.5 ppm). 17 Zhu et al prepared a kind of 3.9% Ag@UG-NiO sensor whose response to 100 ppm butanone was about 3.1 times higher than that of pure porous spherical NiO. 18 Currently, according to literature reports, researchers have improved the response value and recovery speed of sensors by constructing heterostructures, 19 metal ion doping, 20 regulating the micromorphology 16 and light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Direct growth of 2D-TMDs on 3D structured metallic substrates via the CVD method holds promise for the fabrication of high-performance contact interfaces in the 3D integration technology field. [20][21][22][23] Such a chemical reaction process, occurring on the surface of 3D-metals, often allows chemical interaction with the surrounding vapor phase environment that induces the formation of a second phase suitable for multifunctional applications. [24][25][26][27] For instance, a highly ordered 1D intermediate crystal was observed between the MoO 2 substrate and the product 2D MoS 2 obtained through thermal sulfidation, and the subsequent thickening of MoS 2 caused a transition from a p-type to an n-type Schottky contact.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the target molecule reacts with the oxygen ion species on the surface, causing a change in the EDL or HAL, resulting in sensitive detection even at very low concentrations. The main advantages of MOS sensors are low cost, sensitive detection at very low concentrations, facile operation, small size, and facile integration into an integrated circuit (IC). …”
mentioning
confidence: 99%